Keeping cargo security costs down: A risk-based approach to air cargo airport security in small and medium airports. (June 2017) - Amorim da Cunha, Duarte; Macário, Rosário; Reis, Vasco
Abstract: European Union regulations are not sensible to the proportionality of measures and provide fixed orientations and standards irrespective from the dimension of the airports. Additional security measures have been added over the years resulting in increasing security-related costs. The cost structure of security exhibits the existence of a relevant fixed component, concerning staff, equipment, or certification. Notable, smaller, and medium airports support higher costs of security than larger airports, due to the low volumes of cargo and passenger movements. Alternative approaches, notably risk based, have been advocated to support the definition of security procedures at airport level. Although studies have been conducted, none was found concerning these types of airports. This paper presents a research aimed to analyse the appropriateness of a risk based approach in the context of small to medium airports. The research focused in understanding whether such approach could provide tailored security requirements and, ideally, lower costs. A case study considering six airports - Horta, Lisbon, and Ponta Delgada (Portugal), and Adana Şakirpaşa, Erkilet International and Istanbul (Turkey) - of different sizes and located in different regions was conducted. The results make evident the advantages of a risk based approach to define appropriate security procedures, although it is not evident that a risk based approach will lower costs. Highlights: Stricter regulation has been imposed resulting in increasing security-related costs. Literature in air cargo security domain is scares. Six airports with different sizes and geographic/political scenarios were considered. Risk-based approach seems suitable to define appropriate security procedures.